A tailored bifunctional carbon catalyst for efficient glycosidic bond fracture and selective hemicellulose fractionation. (October 2022) - Sun, Chihe; Wu, Wenbo; Chang, Haixing; Wang, Rupeng; Wang, Ke; Zhong, Nianbing; Zhang, Ting; He, Xuefeng; Sun, Fubao; Zhang, Ezhen; Ho, Shih-Hsin
Graphic abstract: Highlights: A magnetic bifunctional solid acid catalyst with polydopamine coating was prepared. Catalysts bearing catalytic SO3 H and adsorption Cl sites preserved porous structure. Catalysts exerted effective bond fracture and selective hemicellulose fractionation. Catalyst surface structure and Cl-functionalized site were important for adsorption. Catalysts exhibited simple separation with good thermal stability and reusability. Abstract: This study proposed a mild chlorination-sulfonation approach to synthesize magnetic carbon acid bearing with catalytic SO3 H and adsorption Cl bifunctional sites on polydopamine coating. The catalysts exerted good textural structure and surface chemical properties (i.e., porosity, high specific surface area of >70 m 2 /g, high catalytic activity with 0.86–1.1 mmol/g of SO3 H sites and 0.8%–1.9% of Cl sites, and abundant hydrophilic functional groups), rendering a maximum cellobiose adsorption efficiency of ∼40% within 6 h. Moreover, the catalysts had strong fracture characteristics on different α–/β–glycosidic bonds with 85.4%–93.9% of disaccharide conversion, while selectively fractionating hemicellulose from wheat straw with 64.3% of xylose yield and 93.4% of cellulose retention. Due to the stable interaction between parent polydopamine support with Fe core and functional groups, the catalysts efficiently recovered by simple magnetic separation had good reusability with minimal losses in catalytic activity.